Partisipasi Masyarakat Dalam Pembentukan RUU Tindak Pidana Kekerasan Seksual Dihubungkan Dengan Asas Pembentukan Undang-Undang Yang Baik - Mangar, Irma; Anshari Pikahulan, Muis Saifuddin; Alamanda, Asri Elies (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Sekolah Tinggi Agama Islam Mulia Astuti (STAIMAS) Wonogiri, 2024)
Regulations are constantly changing as a result of social growth. Political, economic, social, and cultural progress, as well as technological and scientific (information and technological) progress and people's mentality, are all factors to consider. Some strong factors influence actual development, among others: people's way of thinking/outlook on life, aspirations and demands for justice, This legal research tries to solve difficulties or problems by collecting points of view or opinions from various legal professionals, with the aim of providing the right perspective. The concept of enacting this law, which puts the public interest first, requires an independent and autonomous parliament, Participation is not enough just for a handful of people sitting in representative institutions because institutions and people sitting in representative institutions often use politics to fight for their own personal or group interests in the name of the interests of the people. Community participation is a crucial component in producing responsive legal products